Evaluating the Subject-Performed Task effect in healthy older adults: Relationship with neuropsychological tests - Silva, A. R. (2015)
Background An enhancement in recall of simple instructions is found when actions are performed in comparison to when they are verbally presented – the subject-performed task (SPT) effect. This enhancement has also been found with older adults. However, the reason why older adults, known to present a deficit in episodic memory, have a better performance for this type of information remains unclear. In this article, we explored this effect by comparing the performance on the SPT task with the performance on other tasks, in order to understand the underlying mechanisms that may explain this effect. Objective We hypothesized that both young and older adult groups should show higher recall in SPT compared with the verbal learning condition, and that the differences between age groups should be lower in the SPT condition. We aimed to explore the correlations between these tasks and known neuropsychological tests, and we also measured source memory for the encoding condition. Design A mixed design was used with 30 healthy older adults, comparing their performance with 30 healthy younger adults. Each participant was asked to perform 16 simple instructions (SPT condition) and to only read the other 16 instructions (Verbal condition – VT). The test phase included a free recall task. Participants were also tested with a set of neuropsychological measures (speed of processing, working memory and verbal episodic memory). Results The SPT effect was found for both age groups; but even for SPT materials, group differences in recall persisted. Source memory was found to be preserved for the two groups. Simple correlations suggested differences in correlates of SPT performance between the two groups. However, when controlling for age, the SPT and VT tasks correlate with each other, and a measure of episodic memory correlated moderately with both SPT and VT performance. Conclusions A strong effect of SPT was observed for all but one, which still displayed the expected aging deficit. The correlations and source memory data suggest that the SPT and VT are possibly related in respect to their underlying processes, and SPT, instead of being an isolated process, is in connection with both the episodic memory and executive function processes. Under these circumstances, the SPT seems to contribute to an enhancement of the episodic memory trace, presumably from the multimodality it provides, without involving a separated set of cognitive mechanisms. Future research using more pure measures of other cognitive processes that could be related to SPT is necessary.